The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s11010-005-3457-6
|View full text |Cite
|
Sign up to set email alerts
|

H2O2-induced changes in mitochondrial activity in isolated mouse pancreatic acinar cells

Abstract: This study employed confocal laser scanning microscopy to monitor the effect of H2O2 on cytosolic as well as mitochondrial calcium (Ca2+) concentrations, mitochondrial inner membrane potential (psi m) and flavine adenine dinucleotide (FAD) oxidation state in isolated mouse pancreatic acinar cells. The results show that incubation of pancreatic acinar cells with H2O2, in the absence of extracellular Ca2+ ([Ca2+],) led to an increase either in cytosolic and in mitochondrial Ca2+ concentration. Additionally, H2O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…It is therefore possible that the PMCA has an intimate dependence on functional mitochondria. In addition, oxidants have been shown extensively to impair mitochondrial function (30,54). We therefore examined the effects of three mechanistically distinct mitochondrial inhibitors to test if these have similar effects to H 2 O 2 .…”
Section: Validation Of Pmca Activity Assaymentioning
confidence: 99%
“…It is therefore possible that the PMCA has an intimate dependence on functional mitochondria. In addition, oxidants have been shown extensively to impair mitochondrial function (30,54). We therefore examined the effects of three mechanistically distinct mitochondrial inhibitors to test if these have similar effects to H 2 O 2 .…”
Section: Validation Of Pmca Activity Assaymentioning
confidence: 99%
“…CCK can evoke oscillatory Ca 2+ signals and substantial mitochondrial Ca 2+ uptake in pancreatic acinar cells [4041]. H 2 O 2 can cause mitochondrial Ca 2+ release abolished by pretreatment of FCCP or CCCP, a mitochondrial uncoupler [4041]. However, in another study, mitochondrial Ca 2+ uptake did not occur in unstimulated resting cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously suggested that, when working with dual wavelength-excited fluorescent dyes, if one of the lines is affected by the experimental procedures, the wavelength not affected can be successfully employed for the determinations (Gonzalez et al 2005). Following these directions, data of fluorescence at 380 nm excitation light were normalized to the basal (resting) fluorescence values.…”
Section: Analysis Of Intracellular Free-camentioning
confidence: 99%